Statistical analysis of economic poverty in Poland using R - Brzezińska, Justyna (Statystyczna analiza ekonomicznego ubóstwa w Polsce z wykorzystaniem programu R, 2018)
Economic poverty is one of the more common and complex problems in the modern world, as well as in Poland. This is a complex and multidimensional phenomenon, and therefore there is no single universally valid definition of poverty. This article presents a statistical analysis of economic poverty in Poland based on real data from the Central Statistical Office of Poland. An in-depth statistical analysis of the social situation of Poles will be presented, as well as an attempt to examine interdependencies in the occurrence of various forms of poverty and social exclusion in Poland. In the article, several multivariate statistical methods are presented together with the graphical presentation of results. We present a correspondence analysis with a perception map, as well as the advanced modern visualizing tool for categorical data. All the calculations were conducted using R software
Econometrics = Ekonometria, 2018, Vol. 22, No. 2, s. 45-53
Keywords: economic poverty; multivariate statistical analysis; categorical data analysis; R software; ubóstwo ekonomiczne; wielowymiarowa analiza statystyczna; analiza danych jakościowych; program R